2017
DOI: 10.1080/14767058.2017.1393066
|View full text |Cite
|
Sign up to set email alerts
|

Prospective parents’ perspectives on antenatal decision making for the anticipated birth of a periviable infant

Abstract: Our findings underscore the importance of presenting clear information on disability and eliciting the factors that parents deem most important in making decisions about periviable birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…It also speaks to potential gaps in counseling by health care providers. Understanding these gaps is an important research effort of our group as well as others [12]. We hope that the information generated by this pilot study will lead to a larger, comprehensive review of online resources available to patients facing a periviable birth.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It also speaks to potential gaps in counseling by health care providers. Understanding these gaps is an important research effort of our group as well as others [12]. We hope that the information generated by this pilot study will lead to a larger, comprehensive review of online resources available to patients facing a periviable birth.…”
Section: Discussionmentioning
confidence: 93%
“…The American College of Obstetricians and Gynecologists, the Society for Maternal Fetal Medicine, and the American Academy of Pediatrics all emphasize the need for shared decision making regarding interventions for infants born during the periviable period [21,22]. Given patients frequently access the Internet for supplemental health information when faced with medical decision making, we sought to provide data regarding the quality of online information as it pertains to periviable delivery [11,12]. Our work revealed that the overwhelming majority of websites do not address content considered essential for patient education about the difficult decisions surrounding periviable birth.…”
Section: Discussionmentioning
confidence: 99%
“…The second exercise addressed key considerations or factors that have been identified in prior literature and through our own patient‐engaged pilot work as values parents apply in addition to baby's well‐being when considering periviable management decisions. Participants received 10 index cards—seven cards each listing a consideration and three blank cards to write any considerations that were not otherwise listed: (a) “religious or spiritual beliefs”, (b) “Financial concerns”, (c) “social support”, (d) “impact on marriage or relationship”, (e) “impact on your other children”, (f) “impact on your career or work life”, and (g) “impact on your physical or mental health”.…”
Section: Methodsmentioning
confidence: 99%
“…The final exercise addressed the concept of “gist”, which strives to capture and distil individual mental representations related to their options and outcomes . Participants were asked whether they agreed or disagreed with each of the following statements: (a) “Any amount of life is better than no life at all”, (b) “A short comfortable life is better than a long painful life”, (c) “Even a poor or bad “quality of life” is better than no life at all”, (d) “Choosing not to resuscitate would feel like ‘giving up’ on my child”, (e) “Choosing resuscitation would lead to too much suffering for my child”, and (f) “There are some disabilities that I would consider to be worse than death for my child”.…”
Section: Methodsmentioning
confidence: 99%
“…Women and families must navigate this uncertainty to make time-sensitive and value-laden decisions regarding obstetrical interventions for fetal benefit and neonatal care when periviable birth is imminent. Women facing periviable birth have expressed a desire for supplemental information after provider counseling [9][10][11][12][13]. Increasingly, patients are turning to the Internet for supplemental health information.…”
Section: Introductionmentioning
confidence: 99%